The early modern age in secondary education textbooks in Spain: An analysis of activities - Simón-García, María Del Mar (Frontiers in Education, 2023)
The objective of this study is to analyse how the Early Modern Age is taught in secondary school textbooks in Spain. To do so, the study is focused on the analysis of the historical contents of this period, in relation to the topics proposed by historiographical trends. In addition, the textbook activities has been analised according to their type, cognitive level and the historical skills required of secondary students. The sample consists of a total of 770 activities. A mixed methodology has been used, combining quantitative and qualitative techniques. The results obtained indicate that the textbooks have improved in the type of activities and in the cognitive level required, but continue to dominate the contents of concepts, facts and concrete data (related to political and cultural history). On the other hand, the textbooks present a discourse which does not debate or reflect in the development of many of the historiographical stereotypes of the nation, neither does it examine in depth the social problems of the Early Modern Age.